NON-PARTICIPATION OF GRADUETES OF THE SOCIAL WORK IN THE LABOUR MARKET - Melytė, Monika; Milkintaitė, Laima (PROFESSIONAL STUDIES: Theory And Practice, 2024)
The problem of non-participation of graduates in the labour market prevails in the field of social work. Non-participation in the labour market is equated with non-employment on the basis of the available education in social work area. Although social work studies are carried out by most higher education institutions, to which not a small number of graduates enter every year, but the need for social workers in the labour market remains. The aim of this study is to analyse the non participation of social work graduates in the labour market. The study involved 8 social work graduates who graduated from X higher education institutions and did not enter the labour market in accordance with the acquired profession. According research data, non-participation is influenced by changing motivation to work in the studies process, which influences dissatisfaction with professional activities.